Implementasi Sistem Pakar Menggunakan Metode Forward Chaining Untuk Mendiagnosa Penyakit Rahim - Yusuf, Diana; Terisia, Vany (ITB Ahmad Dahlan Jakarta, 2021)
The problem at the present time, especially in the field of health is part obstetrics uterine disease that causes high mortality rates in women , not only in the country of Indonesia is also the world . This happens due to the high number of deaths of women who develop uterine disease . Lack of information and knowledge on diseases of the uterus also cause new problems to the high rate of mortality. The public does not know the symptoms and attack patterns of uterine disease is due to a lack of information about the disease of the uterus. Application of expert system is a computer -based expert system that uses facts and reasoning techniques to solve problems that typically can only be solved by an expert or a doctor . The application of expert systems produce the output of an application program that can be used to diagnose diseases of the uterus in women based on facts or symptoms experienced by users. The method used is forward chaining. Testing the system with forward chaining method begins with questions about the facts or the symptoms experienced user, then the resulting conclusions based on the results of the analysis system .